Language used to Address Women in English and Uzbek and the Historical Context of Their Development (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article aimed to analyze addressing in a special situation in the communication process. While speaking people need to address and in that situation they address to human. And all concept named as a “etiquette”. The etiquette plays important role in society. Linguists think that etiquette is a component of communication and a controller of effective communication. Addressing distinguishes by countries.